Evaluating the Effectiveness of EU Sanctions On Russian Financial Markets: A Garch-Based Approach - Chernykh, Aleksandr (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
This study assesses the efficiency of European Union sanctions imposed on Russia in 2022–2023, focusing on their short- and mid-term impact on financial markets. Despite Russia’s restrictions on macroeconomic and international trade statistics, stock market data remains accessible, allowing an empirical investigation of market responses. Using a CCC-GARCH model, particularly conditional covariance estimation, the study analyzes volatility spillovers and contagion effects across Russian financial markets: stock, government bond, and foreign exchange markets. The findings identify key turbulence periods and the "first domino knuckle"—the initial markets most affected—shedding light on market resilience and shock transmission. Since all the sanctions remain in place and new ones continue to be imposed, assessing their long-term effects is not yet possible. However, this study could provide valuable insights on the effectiveness of economic sanctions and contribute to the broader discourse on economic coercion and market stability.